2003
DOI: 10.1142/s0218625x03005487
|View full text |Cite
|
Sign up to set email alerts
|

Initial Stage of CaF2/Si(111) Epitaxy Investigated by Lateral/Atomic Force Microscopy

Abstract: The initial stages of the high temperature (~ 700°C) MBE growth of CaF 2 on well-oriented Si(111) substrates have been studied by atomic force microscopy (AFM) and lateral force microscopy (LFM) in the atmosphere. At these temperatures CaF 2 molecules react with the silicon surface and form a CaF 1–Si interface layer. The CaF 1 layer covers the silicon surface completely before CaF 2 islands start to form, and it is stable in the atmospheric environment for some days. The subsequent growth on this interface la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Thus, the following analysis assumes the existence of an interface layer with CaF 1 stoichiometry. With this result, the island types identified here are different from the two island types on a multilayer sample observed by Wang et al [61] and, additionally, we can exclude high-temperature interface reconstructions due to an F:Ca ratio falling significantly below 1 [37]. Furthermore, as all experiments were performed under ultra-high-vacuum conditions, we are confident that we do not investigate a contaminated surface after air exposure [22,30].…”
Section: Discussionsupporting
confidence: 46%
See 3 more Smart Citations
“…Thus, the following analysis assumes the existence of an interface layer with CaF 1 stoichiometry. With this result, the island types identified here are different from the two island types on a multilayer sample observed by Wang et al [61] and, additionally, we can exclude high-temperature interface reconstructions due to an F:Ca ratio falling significantly below 1 [37]. Furthermore, as all experiments were performed under ultra-high-vacuum conditions, we are confident that we do not investigate a contaminated surface after air exposure [22,30].…”
Section: Discussionsupporting
confidence: 46%
“…A small number of studies have been performed using atomic force microscopy, most of them in contact mode [34,[60][61][62]. Recently, Klust et al presented materialdependent [63] as well as atomically resolved [64] data using in vacuo frequency-modulated NC-AFM, identifying the CaF 1 and CaF 2 areas and revealing the atomic lattice with similar contrast as has been observed before on (111) surfaces of CaF 2 crystals [65,66].…”
Section: Properties Of the Caf 2 /Si(111) Systemmentioning
confidence: 81%
See 2 more Smart Citations
“…Meanwhile, some CaF 2 molecules nucleate on CaF terraces. In our previous work, 26,27 we observed that some parts of the CaF interface layer were disturbed by thermal decomposition at 700°C. 9 and 23, and a nonuniform CaF 2 film will be obtained, as depicted in Fig.…”
Section: B Morphology At Growth Temperatures Above 510°cmentioning
confidence: 84%